Great Transformation in Eurasia - Katman, Filiz (Cambridge Scholars Publishing, 2018)
This book provides information on the ongoing transformation of the Eurasian region, offering a theoretical background and a discussion of the security complex characteristics of Eurasia, the roles of the ""New Great Game"", and recent opportunities and challenges in the region, such as the new Silk Road. It examines the changes that are taking place beyond the dissolution of the Soviet Union, independence, and the energy and security parameters in the Eurasian region. Eurasia, with its various historical, geographic, economic and socio-political characteristics, its energy resources, transpor